Factors Affecting Behavioral Intention of Tourists to Travel into Local Destinations in Rayong Province, Thailand - Sujira Vuthisopon; Fernando Sampaio; Chutimant Boonnual (My University, 2023)
Purpose: This study aims to explore the factors affecting behavioral intention of tourists to travel into local destinations in Rayong Province, Thailand and to examine destination personality, tourist connection with destination, and tourists’ behavioral intention to visit the local tourist attractions in Rayong province. In addition, the study explored on the influences from the self-brand connection as the transmission factor from destination personality to the behavioral intention for visitation. Theoretical framework: Destination Personality consisting of (1) conviviality, (2) sincerity, (3) excitement influence Self-brand connections which lead to Behavioral intention of revisiting intention and recommendation intention. Methodology: This was quantitative research that used questionnaire to collect data from 385 tourists. Data were analyzed by Structural Equation Model (SEM) Results and conclusion: The destination personality and self-brand connection had the influences on the behavioral intention to visit the destination confirmed by the empirical results stating that the brand connection are the transmission factor of destination personality toward the behavioral intention to travel. Research Implications: This study benefits the tourism industry in Rayong province to realize the behavioral intention of tourists to travel into local destinations in Rayong Province so they can improve their destination personality and brand connection in order to gain revisiting of tourists. Originality value: This study presents the new knowledge of destination personality and tourist attraction brand connection that they are related and have direct influences on tourist intentions to revisit the place.
Keywords: Consumer Behavior in Brand Consumption and Identification